Large fetal intra‐abdominal umbilical vein varix: Antenatal sonographic diagnosis and follow‐up. Issue 9 (25th June 2019) - Gowda, Sunil; Chakkalakkoombil, Sunitha V.; Bharathi, Shree; Barathi, Deepak
Abstract: Fetal intra‐abdominal umbilical vein varix is an uncommon antenatal finding defined as focal dilatation of umbilical vein >9 mm or more than two standard deviations above the mean for the gestational age. We report the case of a 28‐year‐old gravida 2 diabetic lady, who presented at 35 weeks of gestation, whose antenatal ultrasonography showed a cystic lesion of size 4 × 3.8 cm showing turbulent venous flow in the fetal abdomen in continuity with the umbilical vein, diagnosed as umbilical vein varix without any other anomaly. Postnatal ultrasonography showed size reduction and thrombosis of varix. Isolated umbilical vein varix has a favorable outcome, whereas those associated with other structural anomalies have a variable prognosis. This case was reported because of the unusually large size of varix with a good outcome and also to stress the importance of detailed sonography and close fetal monitoring in the presence of umbilical vein varix.